Isotopic tracing of hydrogen transport and trapping in nuclear materials. (28th July 2017) - Chêne, Jacques; Martin, Frantz
Abstract : Some illustrations of the use of deuterium or tritium for isotopic tracing of hydrogen absorption, transport and trapping in nuclear materials are presented. Isotopic tracing of hydrogen has been shown to be successful for the determination of the boundaries conditions for hydrogen desorption or absorption in a material exposed to a hydrogen source. Also, the unique capabilities of isotopic tracing and related techniques to characterize H interactions with point defects and dislocations acting as moving traps has been demonstrated. Such transport mechanisms are considered to play a major role in some stress corrosion cracking and hydrogen embrittlement mechanisms. This article is part of the themed issue 'The challenges of hydrogen and metals'.